Review of the scientific journal “Agroindustria, Sociedad y Ambiente” (issn 2343-6115) of the Universidad Centroccidental Lisandro Alvarado (Revista Electrónica REDINE, 2021)
This review describes the process of creation and consolidation of the scientific journal "Agroindustria, Sociedad y Ambiente" (ISSN 2343-6115) of the Universidad Centroccidental Lisandro Alvarado, Venezuela. This means of scientific dissemination was founded in 2013, attached to the Dean of Agronomy of said university, published biannually, and with the purpose of contributing to the dissemination of scientific articles by national and international researchers about productive systems, technology of products of plant and animal origin, physiology and post-harvest treatments, food quality, functional foods, food microbiology, ecology and environmental problems, biotechnology, technology transfer and education.
Keywords: scientific journal; agroindustry; UCLA; university; Venezuela